Are alternative food networks winning strategies to increase organic SMEs profitability? Evidence from a case study. (28th February 2020) - Testa, Riccardo; Galati, Antonino; Schifani, Giorgio; Crescimanno, Maria; Trapani, Anna Maria Di; Migliore, Giuseppina
The aim of this study was to understand how and how much alternative food networks (AFNs) contribute to increasing the profitability of the organic SMEs, compared to traditional organic sales channels. For this purpose, an economic analysis and an in-depth interview were carried out in a case study located in the Sicilian northern coast. Findings showed a clear convenience of the participation to alternative food networks compared to the case in which all farm production was conferred to traditional sales channels, highlighting an increase both of farm profit (+76.9%) and net income (+72.1%). However, the in-depth interview revealed that AFNs are a mean, not only to have economic benefits, but also to satisfy consumers' social and environmental needs. According to the findings of this study, alternative food networks could represent a strategy to increase the profitability of many small and medium-sized farms (organic and non-organic) managed by the farmer and his family, especially in an increasingly global and diversified market.